Nucleic Acid-conjugated Carbohydrate Nanobiosensors: A Multimodal Tool for Disease Diagnosis - Kantak, Maithili; Shende, Pravin (Current Pharmaceutical Design, 2022)
Background: Nucleic acid-based carbohydrate sensors (NAbCSs) constitute a strategy involving nucleic acids as recognition elements for the development of a unique, stable, sensitive, mono- or multimodal detection system in the field of nanomedicine, gas sensing, and gene therapy. Thus, this advanced platform for next-generation investigation compromises cost-effective, wearable, and noninvasive sensing devices as diagnostics in healthcare. Objective: This review article highlights the importance of NAbCSs and explores the novel applications of sensors fabricated via the conjugation of nucleic acids and carbohydrates. Additionally, advances in smart portable devices, like smartphones, printers, and digital multimeters, are summarized, followed by the challenges involved in the development of futuristic sensing tools. Methods: A novel platform has been unfolded for the detection of different chemical toxins (like aflatoxin B1, ochratoxin A) and biomarkers (like miRNA in cancer) present in biosamples, food and biowarfare agents. The potential applications of biosensing in the areas of miniaturization, reusability, rapid, point-of-care or portable for home analysis techniques, cost-effective, eco-friendly, high throughput and personalized sensors for qualitative analysis of target analyte/s in bio-fluids and food have been explored. Conclusion: NAbCSs provide real-time monitoring of biosamples qualitatively and semi-quantitatively (luminometer, fluorimeter, etc.) in the absence of trained personnel. Explorations of NAbCSs encompass advantages in remote resource-limited access areas with simultaneous monitoring via smart devices for multiple analytes with greater precision, sensitivity, and selectivity.
Keywords: aptasensors